Spine and Thoracic Height Measurements Have Excellent Interrater and Intrarater Reliability in Patients With Early Onset Scoliosis. Issue 4 (15th February 2018) - Michael, Nicole; Carry, Patrick; Erickson, Mark; Bloch, Nikki; Gibbons, Steven; O'Donnell, Courtney; Garg, Sumeet
Abstract : Study Design: Reproducibility of measurements. Objective: This study investigates the reliability and standard error of measurement of spine and thoracic height radiographic measurements in patients with early onset scoliosis (EOS). Summary of Background Data: Spine and thoracic height radiographic measurements are often used as a surrogate for pulmonary development in patients with EOS. There is limited literature validating the reliability of spine and thoracic height measurements in the EOS population. Methods: Using pilot data, we determined measuring 49 unique radiographs would provide 80% power to obtain a 95% confidence interval (CI) width of 0.05 for the interclass correlation coefficients (ICCs). A random sampling strategy, stratified by underlying diagnosis from the Classification of Early Onset Scoliosis (C-EOS), was used to distribute the diagnoses in the study sample. Two attending pediatric spine surgeons, two pediatric orthopedic fellows, and two research assistants measured coronal spine (T1-S1) and thoracic (T1-T12) height on digital radiographs using imaging software (Surgimap; Nemaris, Inc, New York) on two separate occasions at least 3 weeks apart. Order of images was randomized for the second iteration. Linear mixed model regression analyses were used to estimate interrater and intrarater reliability. Results: The study sample included subjects (N = 48) with idiopathic (N = 17, 35%), congenital (N = 16, 33%, 1 patient excluded), neuromuscular (N = 11, 23%), and syndromic (N = 4, 8%) scoliosis. Overall interrater reliability estimates for spine height (ICC: 0.894, 95% CI: 0.847–0.932) and thoracic height (ICC: 0.890, 95% CI: 0.844–0.929) were excellent. Intrarater reliability estimates for spine height (ICC: 0.906, 95% CI: 0.830–0.943) and thoracic height (ICC: 0.898, 95% CI: 0.817–0.938) were also excellent. Conclusion: There is excellent interrater and intrarater reliability for radiographic measurements of spine and thoracic height in the EOS population at our institution. Level of Evidence: 2